Design and fabrication of smart composites - Tan, Kai Yong. (2010)
In recent years, hybrid composites consisting of shape memory alloys (SMA) and carbon fiber reinforced plastics (CFRP) have attracted the attention of the aviation industry, especially since CFRP is widely used in aerospace technologies. CFRP embedded with SMA, also known as SMA adaptive composites, have been studied and known to be capable of suppressing microscopic mechanical damages in the polymer matrix of CFRPs. This property has immense potential in terms of increasing the reliability and integrity of current aerospace composite structures. This final year project focuses on the design, fabrication and analysis of TiNi embedded CFRP hybrid composites. In this study, the SMA adaptive composites are first prepared using a specially designed fixture, followed by vacuum bagging and autoclave curing procedures. In the experiments, the fabricated adaptive composites are tested for shape memory effect by mounting surface strain gages and activation of two-way shape memory effect is achieved via joule resistance heating. The cross-section microstructures of the adaptive composites are then studied under the Scanning Electron Microscope. Experimental data suggests that the adaptive composites are capable of two-way shape memory effect. The conclusion of this study is that there is a trend of increasing quantity and size of voids and cavities present in the structure of the adaptive composite specimens as the volume fraction of embedded Nitinol wires increases. Factors such as degree of fiber wetting, drapeability of prepreg, relative diameters of constituent reinforcement fibers and fabrication conditions are suspected to be key contributors to the above trend. Lastly, problems and recommendations for future studies related to the project are discussed, rounding off Nanyang Technological University’s pioneer attempt at smart composite design and fabrication.